Enabling Virtual Learning for Biomechanics of Tooth Movement: A Modified Nominal Group Technique - Fakhitah Ridzuan; Gururajaprasad Kaggal Lakshmana Rao; Rohaya Megat Abdul Wahab; Maryati Md Dasor; Norehan Mokhtar (MDPI AG, 2023)
Virtual learning is a medium that can enhance students' understanding of a specific topic. The emergence of the COVID-19 pandemic provided an opportunity for dental education to shift from traditional learning to blended learning as it began to utilize technology to help students study effectively. In this study, we collaborated with experts in the field of dentistry to reach a consensus about which topics are appropriate to include in the virtual learning module about the biomechanics of tooth movement. We convened a panel of five experts who had a minimum of two years of experience in teaching orthodontics and introduced them to the Nominal Group Technique (NGT), which is a well-established, organized, multistep, assisted group meeting technique for generating consensus. The following ten key topics were identified for inclusion in the module: physiology of tooth movement; tooth movement-definition, type, theory, indications; force systems; anchorage; fixed appliances; biomaterials related to tooth movement; removable appliances; factors affecting tooth movement; iatrogenic effect of tooth movement; and current advances and evidence regarding tooth movement. The modified NGT approach led to the development of a ranked thematic list of the topics related to the biomechanics of tooth movement that can be delivered to students via virtual learning.